The Mid-Infrared Instrument for the James Webb Space Telescope, X: Operations and Data Reduction. (4th January 2016) - Gordon, Karl D.; Chen, C. H.; Anderson, Rachel E.; Azzollini, Ruymán; Bergeron, L.; Bouchet, Patrice; Bouwman, Jeroen; Cracraft, Misty; Fischer, Sebastian; Friedman, Scott D.; García-Marín, Macarena; Glasse, Alistair; et al.
Abstract: We describe the operations concept and data reduction plan for the Mid-Infrared Instrument (MIRI) for the James Webb Space Telescope ( JWST ). The overall JWST operations concept is to use observation templates (OTs) to provide a straightforward and intuitive way for users to specify observations. MIRI has four OTs that correspond to the four observing modes: (1) imaging, (2) coronagraphy, (3) low-resolution spectroscopy, and (4) medium-resolution spectroscopy. We outline the user choices and expansion of these choices into detailed instrument operations. The data reduction plans for MIRI are split into three stages, where the specificity of the reduction steps to the observation type increases with stage. The reduction starts with integration ramps: stage 1 yields uncalibrated slope images; stage 2 calibrates the slope images; and then stage 3 combines multiple calibrated slope images into high-level data products (e.g., mosaics, spectral cubes, and extracted source information). Finally, we give examples of the data and data products that will be derived from each of the four different OTs.